Numerical study of kerosene spray and combustion characteristics using an air-blast atomizer - I.A. Ibrahim; A.M. Elzallat; M.M. Elsakka; T.M. Farag; H.M. Gad (Energy Reports, 2022)
In this study, a computational model for a cylindrical combustor with an air-blast atomizer was created to investigate the effect of changing air to liquid mass ratio (ALR) on spray characteristics without combustion and the effect of changing ALR on combustion characteristics under different swirl numbers with constant kerosene fuel mass flow rate using computational fluid dynamics (CFD) code. The study aim is to define the ALR at which the pollutants concentrations at combustion exhaust will be the least. Eight values of ALR were considered and these include 0.3, 0.5, 0.7, 0.9, 1.0, 1.2, 1.4 and 1.5. The cold spray characteristics including the number of droplets, Sauter Mean Diameter, droplets penetration length and droplets contours were obtained in addition to combustion characteristics that were studied by describing the reverse flow zone (RFZ) boundary, flow pathlines, temperatures maps, outlet temperatures at combustor exit and species concentrations. The results indicate that increasing ALR and consequently spray droplet diameter decrease does not always translate into superior emissions performance and it depends on several parameters including swirling intensity where the modernistic capabilities of CFD code including flow visualization and calculated recirculated mass flow ratio are used to justify the reasons behind this exceptional behavior. In addition, the results show that the spray Sauter Mean Diameter decreases by increasing ALR but the droplet diameter reduction effect was steeper at lower ALR than higher ones. The length of the RFZ is decreasing with the increase of ALR and shifts upstream closer to the combustor swirler. The recirculated flow mass ratio and the outlet average temperature are decreasing with the increase of ALR.